Functional characterization of a flavonoid glycosyltransferase gene from withania somnifera (Ashwagandha) - Singh, Somesh; Vishwakarma, Rishi. K.; Kumar, R. J. Santosh; Sonawane, Prashant D.; Ruby; Khan, Bashir Mohammad (Applied Biochemistry and Biotechnology, 2013)
Glycosylation of flavonoids is mediated by family 1 uridine diphosphate (UDP)-dependent glycosyltransferases (UGTs). Until date, there are few reports on functionally characterized flavonoid glycosyltransferases from Withania somnifera. In this study, we cloned the glycosyltransferase gene from W. somnifera (UGT73A16) showing 85-92 % homology with UGTs from other plants. UGT73A16 was expressed as a His(6)-tagged fusion protein in Escherichia coli. Several compounds, including flavonoids, were screened as potential substrates for UGT73A16. HPLC analysis and hypsochromic shift indicated that UGT73A16 transfers a glucose molecule to several different flavonoids. Based on kinetic parameters, UGT73A16 shows more catalytic efficiency towards naringenin. Here, we explored UGT73A16 of W. somnifera as whole cell catalyst in E. coli. We used flavonoids (genistein, apigenin, kaempferol, naringenin, biochanin A, and daidzein) as substrates for this study. More than 95 % of the glucoside products were released into the medium, facilitating their isolation. Glycosylation of substrates occurred on the 7- and 3-hydroxyl group of the aglycone. UGT73A16 also displayed regiospecific glucosyl transfer activity towards 3-hydroxy flavone compound, which is the backbone of all flavonols and also for a chemically synthesized compound, not found naturally. The present study generates essential knowledge and molecular as well as biochemical tools that allow the verification of UGT73A16 in glycosylation.
Keywords: Flavonoid; glycosylation; Glycosyltransferase; Hypsochromic shift; Plant secondary product glycosyltransferase (PSPG); Withania somnifera